2015
DOI: 10.1111/bjdp.12104
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of the relationship between maternal mind‐mindedness and theory of mind

Abstract: Data are presented from a longitudinal investigation examining the relationship between maternal mind-mindedness (MM) in infancy and socio-cognitive development in childhood. We revisited children (n = 18) who had taken part in a longitudinal study as infants. MM had been assessed at 10, 12, 16, and 20 months of age. We followed up these children at 5-6 years of age to test their higher order theory of mind (ToM) (using the strange stories task). The convergent validity, temporal stability, and predictive vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 28 publications
2
46
1
2
Order By: Relevance
“…In line with prior research, appropriate mind‐related comments were stable over time in both mothers and fathers (e.g., Kirk et al., 2015). Non‐attuned comments were only stable for fathers.…”
Section: Discussionmentioning
confidence: 99%
“…In line with prior research, appropriate mind‐related comments were stable over time in both mothers and fathers (e.g., Kirk et al., 2015). Non‐attuned comments were only stable for fathers.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal mentalization is considered an important precursor of various aspects of infants' cognitive and social development. Online maternal mentalization during infancy has been positively associated with children's language acquisition in toddlerhood (Laranjo & Bernier, ), executive functioning (Bernier, Carlson, Deschênes, & Matte‐Gagné, ), school readiness in preschool (Bernier et al., ), and theory of mind development (e.g., Devine & Hughes, ; Kirk et al., ; Meins et al., ). Furthermore, high prenatal (offline) as well as postnatal (online) maternal mentalization predicts lower levels of internalizing and externalizing behaviors in toddlerhood (Meins, Centifanti, Fernyhough, & Fishburn, ; Smaling, Huijbregts, van der Heijden, van Goozen, & Swaab, ), suggesting that maternal mentalization can buffer against the development of conduct problems (e.g., Hughes, Aldercotte, & Foley, ).…”
Section: Maternal Mentalization and Behaviors During Observed Dyadic mentioning
confidence: 99%
“…Previous research involving biological families has suggested that mindmindedness is relatively stable over time (Illingworth, MacLean, & Wiggs, 2016;Kirk et al, 2015;Meins, Fernyhough, Arnott, Leekam, & Turner, 2001;Meins et al, 2003;McMahon, Camberis, Berry, & Gibson, 2016). But this stability has been observed only within early childhood, and no study has investigated whether mind-mindedness changes in concert with fluctuations in the quality of the relationship.…”
Section: Discussionmentioning
confidence: 99%